2014
DOI: 10.5005/jp-journals-10008-1164
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Control after Trabeculectomy, Phacotrabeculectomy and Phacoemulsification in a Hispanic Population

Abstract: Purpose: To compare the efficacy of different surgical strategies for intraocular pressure (IOP) control in Hispanic glaucoma patients with and without visually significant cataracts.Design: Comparative retrospective consecutive case series.Methods: The charts of 153 consecutive patients with primary open angle glaucoma who underwent either trabeculectomy alone (n = 51), phacotrabeculectomy (n = 51), or phacoemulsification alone (n = 51) were reviewed to compare IOP control, the number of glaucoma medications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Similarly, the mean number of IOP-lowering medications used at 24 months was not statistically significantly different between treatment groups [30], suggesting limited long-term effectiveness of the device. We did not expect to see additional IOP lowering in the phaco + implant group, because many studies looking at trabeculectomy and phaco-trabeculectomy have shown comparable IOP lowering with both procedures [31][32][33][34][35][36][37][38]. Both phacoemulsification and trabeculectomy techniques have evolved, which might explain why more recent papers report no differences in outcomes between trabeculectomy alone vs combined with phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the mean number of IOP-lowering medications used at 24 months was not statistically significantly different between treatment groups [30], suggesting limited long-term effectiveness of the device. We did not expect to see additional IOP lowering in the phaco + implant group, because many studies looking at trabeculectomy and phaco-trabeculectomy have shown comparable IOP lowering with both procedures [31][32][33][34][35][36][37][38]. Both phacoemulsification and trabeculectomy techniques have evolved, which might explain why more recent papers report no differences in outcomes between trabeculectomy alone vs combined with phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…However, fibrosis in the eye may restrict vision or interfere with drainage of aqueous humor and hence might be fatal [104]. Trabeculectomy surgery is considered an option to release the increased ocular pressure [105]. The main purpose of trabeculectomy is to generate a drainage outflow track for the aqueous humor [105].…”
Section: Experimental Outcomes Of Hdac Inhibitors In Animal Modelsmentioning
confidence: 99%
“…Trabeculectomy surgery is considered an option to release the increased ocular pressure [105]. The main purpose of trabeculectomy is to generate a drainage outflow track for the aqueous humor [105]. Scar formation around the outflow track halts drainage, indicating surgical failure.…”
Section: Experimental Outcomes Of Hdac Inhibitors In Animal Modelsmentioning
confidence: 99%
“… 6 The Registry in Glaucoma Outcomes Research (RiGOR) study, no ethnicity-based differences were observed in responses to medical, laser, or surgical interventions for glaucoma. 7 An uncontrolled series of Latinos with glaucoma undergoing phacoemulsification, trabeculectomy, or phacotrabeculectomy demonstrated intraocular pressure (IOP) and IOP-lowering medication reductions consistent with those reported in white patients, 8 while several other studies have found Latino ethnicity to be a risk factor for surgical success following trabeculectomy 9 , 10 and tube-shunt implantation. 11 Regarding minimally invasive glaucoma surgeries, a series of Latinos undergoing combined phacoemulsification and trabecular microbypass implantation manifested IOP and medication reductions consistent with those reported in studies with primarily white patient samples, 12 and Latino ethnicity was a positive prognostic factor for success of trabecular ablation.…”
Section: Introductionmentioning
confidence: 73%